An Analysis of Idiomatic Expressions Used in Percy Jackson’s Novel Entitled Greek Gods - Algifari, Alif Maulana; Nuriadi, Nuriadi; Isnaini, Muh; Baharuddin, Baharuddin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The purpose of this research was to identify the types of idiomatic expressions and to analyze the Idiomatic meanings of idioms used in Rick Riordan’s novel Percy Jackson: Greek Gods. This study implied a descriptive qualitative research design, focusing on the interpretation of meaning, concepts, and linguistic phenomena rather than statistical measurement. The data were collected from the novel and analyzed using Makkai’s idiom classification and a pragmatic stylistic approach based on Grice’s cooperative principles. The findings reveal that there are 118 idiomatic expressions found in the novel, which are classified into six types of idioms, namely phrasal verb idioms, tournure idioms, phrasal compound idioms, incorporating verb idioms, pseudo-idioms, and irreversible binomial idioms. The meanings of the idioms lie in the novel depends heavily on narrative context rather than literal word meanings.